Galectin-3 inhibitor GB0139 protects against acute lung injury by inhibiting neutrophil recruitment and activation - Humphries, Duncan C.; Mills, Ross; Boz, Cecilia; McHugh, Brian J.; Hirani, Nikhil; Rossi, Adriano G.; Pedersen, Anders; Schambye, Hans T.; Slack, Robert J.; Leffler, Hakon; Nilsson, Ulf J.; Wang, Wei; et al. (Frontiers in Pharmacology, 2022)
Rationale: Galectin-3 (Gal-3) drives fibrosis during chronic lung injury, however, its role in acute lung injury (ALI) remains unknown. Effective pharmacological therapies available for ALI are limited; identifying novel concepts in treatment is essential. GB0139 is a Gal-3 inhibitor currently under clinical investigation for the treatment of idiopathic pulmonary fibrosis. We investigate the role of Gal-3 in ALI and evaluate whether its inhibition with GB0139 offers a protective role. The effect of GB0139 on ALI was explored in vivo and in vitro. Methods: The pharmacokinetic profile of intra-tracheal (i.t.) GB0139 was investigated in C57BL/6 mice to support the daily dosing regimen. GB0139 (1−30 µg) was then assessed following acute i.t. lipopolysaccharide (LPS) and bleomycin administration. Histology, broncho-alveolar lavage fluid (BALf) analysis, and flow cytometric analysis of lung digests and BALf were performed. The impact of GB0139 on cell activation and apoptosis was determined in vitro using neutrophils and THP-1, A549 and Jurkat E6 cell lines. Results: GB0139 decreased inflammation severity via a reduction in neutrophil and macrophage recruitment and neutrophil activation. GB0139 reduced LPS-mediated increases in interleukin (IL)-6, tumor necrosis factor alpha (TNF and macrophage inflammatory protein-1-alpha. In vitro, GB0139 inhibited Gal-3-induced neutrophil activation, monocyte IL-8 secretion, T cell apoptosis and the upregulation of pro-inflammatory genes encoding for IL-8, TNF, IL-6 in alveolar epithelial cells in response to mechanical stretch. Conclusions: These data indicate that Gal-3 adopts a pro-inflammatory role following the early stages of lung injury and supports the development of GB0139, as a potential treatment approach in ALI.